Mussel Byssal Attachment Weakened by Anthropogenic Noise - Zhao, Xinguo; Sun, Shuge; Shi, Wei; Sun, Xuemei; Zhang, Yan; Zhu, Lin; Sui, Qi; Xia, Bin; Qu, Keming; Chen, Bijuan; Liu, Guangxu (Frontiers in Marine Science, 2021)
The increasing underwater noise generated by anthropogenic activities has been widely recognized as a significant and pervasive pollution in the marine environment. Marine mussels are a family of sessile bivalves that attach to solid surfaces via the byssal threads. They are widely distributed along worldwide coastal areas and are of great ecological and socio-economic importance. Studies found that anthropogenic noise negatively affected many biological processes and/or functions of marine organisms. However, to date, the potential impacts of anthropogenic noise on mussel byssal attachment remain unknown. Here, the thick shell mussels Mytilus coruscus were exposed to an ambient underwater condition (∼50 dB re 1 μPa) or the playbacks of pile-driving noise (∼70 or ∼100 dB re 1 μPa) for 10 days. Results showed that the noise significantly reduced the secretion of byssal threads (e.g., diameter and volume) and weakened their mechanical performances (e.g., strength, extensibility, breaking stress, toughness and failure location), leading to a 16.95–44.50% decrease in mussel byssal attachment strength. The noise also significantly down-regulated the genes expressions of seven structural proteins (e.g., mfp-1, mfp-2, mfp-3, mfp-6, preCOL-P, preCOL-NG, and preCOL-D) of byssal threads, probably mediating the weakened byssal attachment. Given the essential functions of strong byssal attachment, the findings demonstrate that the increasing underwater anthropogenic noise are posing a great threat to mussel population, mussel-bed community and mussel aquaculture industry. We thus suggest that future work is required to deepen our understanding of the impacts of anthropogenic noise on marine invertebrates, especially these with limited locomotion ability, like bivalves.